SCRAPBOOK LEARNING MEDIA IN CLASS X ECOSYSTEM MATERIALS - Eva Wulan Septiana; Marinda Sari Sofiyana; Devita Sulistiana (Universitas Islam Balitar, 2023)
Based on pre data study obtained results that eye lesson biology on class X high school level in particular Theory ecosystem still impressed difficult for students who have accept learning it's on the spot observation researcher, with reason boring, no interesting, lots memorization, a lot sentence scientific / foreign words and lazy read. Still many student feel the media used the not yet efficient and not enough interesting in the learning process biology. This thing caused on non-maximal learning process teach. as a result student not enough concentration in learning the so that student feel bored and bored, finally the learning process not yet achieved with perfect. Study this aim for knowing appropriateness and quality as well as for knowing response student to learning media scrapbook on Theory ecosystem. Method research used in study this is RND with use developed design by Borg and Gall. Results from study Average score expert the is 91.36 % with criteria very worth. This thing show that quality of learning media scrapbook Theory developed ecosystem _ based on evaluation expert materials, media experts, and expert language very worthy used as a learning medium. Percentage evaluation by field teacher studies of 84.5 % criteria very worth. Whereas acquisition percentage test try scale limited of 95.2 % with criteria very worth. Results from test response student get percentage 90% with criteria very good. From result percentage the then the media can used with good in learning ecosystem class X high school.